Recent innovation in benchmark rates (BMR): Evidence from influential factors on Turkish Lira Overnight Reference Interest Rate with machine learning algorithms - Özer Depren; Mustafa Tevfik Kartal; Serpil Kılıç Depren (Financial Innovation, 2021)
Some countries have announced national benchmark rates, while others have been working on the recent trend in which the London Interbank Offered Rate will be retired at the end of 2021. Considering that Turkey announced the Turkish Lira Overnight Reference Interest Rate (TLREF), this study examines the determinants of TLREF. In this context, three global determinants, five country-level macroeconomic determinants, and the COVID-19 pandemic are considered by using daily data between December 28, 2018, and December 31, 2020, by performing machine learning algorithms and Ordinary Least Square. The empirical results show that (1) the most significant determinant is the amount of securities bought by Central Banks; (2) country-level macroeconomic factors have a higher impact whereas global factors are less important, and the pandemic does not have a significant effect; (3) Random Forest is the most accurate prediction model. Taking action by considering the study's findings can help support economic growth by achieving low-level benchmark rates.
Keywords: C40; E43; E44; G12; 650; Benchmark rate; Determinants; Machine learning algorithms; Turkey